Treatment of severe falciparum malaria: quinine versus artesunate - Patel, Dipesh; Sadatia, Vishal; Patel, Mehul (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Malaria is the most important disease of human being. More than 40% of the world’s population is considered to be at risk of exposure of this disease. Malaria infection has been increasing over recent years due to combination of factors including increasing resistance of malarial parasite. Most of the strains of P. falciparum are now resistance to conventional drugs like chloroquine in many areas. The objective of this study was to compare the efficacy and safety of quinine and artesunate in treatment of P. falciparum malaria. Methods: This is hospital based prospective study, conducted amongst 35 randomly selected patients of severe P. falciparum malaria. Patients with any contraindications of either drug were excluded to avoid bias. Standard statistical tests were applied for qualitative as well as quantitative data. Results: As per the study end point results of difference of mortality in patients receiving either drug was not significant (p > 0.75), but difference in clinical parameters like fever clearance time (p <0.01), parasite clearance time (p < 0.001) and coma resolution time (p < 0.001) were significant among patients receiving artesunate. There were no any significant differences in adverse effects of both the drugs. Mortality was same in both arms taking either drug. Conclusions: Artesunate is as good as quinine in mortality aspect but artesunate is superior in fever clearance time (FCT) & parasite clearance time (PCT). Coma resolution time is faster with quinine as compared to artesunate. There are no significant adverse effects of either drug. So artesunate is equivalent or superior for treatment for severe falciparum malaria.